2019
DOI: 10.1002/jac5.1066
|View full text |Cite
|
Sign up to set email alerts
|

Timing of pharmacist‐clinician collaborative visits after hospital discharge and their effect on readmission risk

Abstract: Objectives The primary objective of this study was to determine whether pharmacist‐clinician collaborative (PCC) visits within 7 days after hospital discharge (early‐visit cohort) would reduce the risk of 30‐day hospital readmission compared with PCC visits eight or more days after hospital discharge (late‐visit cohort). Methods This retrospective study of adult primary care patients was conducted from July 26, 2013 to April 1, 2016. Patients who were included were receiving at least one medication that put th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Few studies have discussed medications as a risk factor for hospital readmission, and some studies have examined postdischarge follow-ups with pharmacist involvement as well. 33,34 However, this study focused specifically on the impact that medication discrepancies have on readmission rates within 30 days of discharge. One study suggested that the quality of medication reconciliation may be associated with the risk of readmission.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have discussed medications as a risk factor for hospital readmission, and some studies have examined postdischarge follow-ups with pharmacist involvement as well. 33,34 However, this study focused specifically on the impact that medication discrepancies have on readmission rates within 30 days of discharge. One study suggested that the quality of medication reconciliation may be associated with the risk of readmission.…”
Section: Discussionmentioning
confidence: 99%